2022
DOI: 10.3389/fpsyt.2022.984829
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of obesity and overweight in Chinese patients with bipolar disorder

Abstract: ObjectDespite abundant literature demonstrating a high prevalence of obesity and overweight in people with bipolar disorder (BD), little is known about this topic in China. Therefore, we assessed the prevalence and associated factors of obesity and overweight among inpatients with BD in our hospital, one of the largest public psychiatric hospitals in China.MethodsIn this retrospective, cross-sectional study, 1,169 inpatients ≥18 years with BD during 2019 were included. Obesity was defined as having a BMI ≥25 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In China, one study found that the prevalence of obesity in patients with BD was 21%. 24 In other countries, studies have explored the prevalence of obesity in patients who were administered medication for BD. 9 Nevertheless, few studies have explored the prevalence of obesity and its risk factors in untreated BD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, one study found that the prevalence of obesity in patients with BD was 21%. 24 In other countries, studies have explored the prevalence of obesity in patients who were administered medication for BD. 9 Nevertheless, few studies have explored the prevalence of obesity and its risk factors in untreated BD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In China, one study found that the prevalence of obesity in patients with BD was 21%. 24 Nevertheless, few studies have explored the prevalence of obesity and its risk factors in untreated BD patients. The prevalence and risk factors for BD with obesity differ significantly between regions and ethnic populations.…”
Section: Introductionmentioning
confidence: 99%